Mainstreaming Biodiversity in Development Practice: Can the Concept of PES Deliver?. (October 2017) - Grima, Nelson; Ringhofer, Lisa; Singh, Simron J.; Smetschka, Barbara; Lauk, Christian
Given the intricate link between biodiversity and poverty, this article critically reflects on the role of mainstreaming biodiversity in development policy and practice. In order to better understand the operational challenges 'on the ground', we present some of the dominant development frameworks within which development organizations operate, all with a view to better understand how aid 'thinks' and 'works'. The article then examines the concept of Payment for Ecosystem Services (PES) as a potential avenue to mainstream biodiversity into development.